2021
DOI: 10.32604/cmes.2021.015300
|View full text |Cite
|
Sign up to set email alerts
|

Self-Driving Algorithm and Location Estimation Method for Small Environmental Monitoring Robot in Underground Mines

Abstract: In underground mine environments where various hazards exist, such as tunnel collapse, toxic gases, the application of autonomous robots can improve the stability of exploration and efficiently perform repetitive exploratory operations. In this study, we developed a small autonomous driving robot for unmanned environmental monitoring in underground mines. The developed autonomous driving robot controls the steering according to the distance to the tunnel wall measured using the light detection and ranging sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In the previous studies for developing autonomous robots utilized in underground mines [22][23][24][25][26], the robots were forced to drive along a simple one-way route. However, this study demonstrated that autonomous robots can drive complex multipoint routes in underground mines while recognizing the road signs using a machine-vision-based algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies for developing autonomous robots utilized in underground mines [22][23][24][25][26], the robots were forced to drive along a simple one-way route. However, this study demonstrated that autonomous robots can drive complex multipoint routes in underground mines while recognizing the road signs using a machine-vision-based algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…In the mining industry, several studies of autonomous driving technology have been conducted in underground mining environments using autonomous robots [16][17][18][19][20][21][22][23][24][25][26]. Baker et al [27] developed "groundhog", an autonomous driving robot that can be used even in underground mines having poor road conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(a) ERP‐42 robot for environmental monitoring in underground mines. Reproduced from Kim and Choi (2021). (b) ARMEx robot based on the Husky A200 platform for remote methane detection and mapping with TDLAS sensor.…”
Section: Mobile Robot Platformsmentioning
confidence: 99%
“…In general, UGVs are better suited to applications which require a denser coverage of gas concentration measurements collected over a long period of time. Some of which include locating and mapping the distribution of methane at landfill sites (Hernandez Bennetts et al, 2012), detecting chemicals in underground mines (Kim & Choi, 2021; Martinez et al, 2020), gas pipeline leakage detection (Kroll et al, 2009), and gas source localization of near ground sources.…”
Section: Mobile Robot Platformsmentioning
confidence: 99%
“…For example, it was used in the form of building a spatial database for a mine site, entering attribute information to visualize it, or performing a pre-simulation by changing attribute information [16][17][18][19]. Recently, high-resolution databases of mining sites have been constructed using drones [20][21][22][23] and unmanned ground vehicles [24][25][26][27][28][29]. Further, small-scale mining sites using a low-power Bluetooth beacon and a smartphone equipped with short-range communication technology are being developed [30][31][32].…”
Section: Introductionmentioning
confidence: 99%